Reações de β-enaminodicetonas com ncn dinucleófilos: obtenção de pirimidinas e sistemas heterocíclicos fundidos - Vargas, Pâmela Schütz de (2016)
In this study the reactivity of β-enamino diketones [RC(O)C(=CHNMe2)C(O)CO2Et, R = C6H5, 4-Me-C6H4, 4-MeO-C6H4, 4-F-C6H4, 4-Br-C6H4, 4-NO2-C6H4, tien-2-il] with NCN bisnucleophiles as amidine and guanidine was investigated. The tiopirimidines ethyl 2-benzylthio-pyrimidine-4-carboxylates, (65-91 %) and Ethyl 2-metiltiopirimidine-4-carboxylates (69-91 %) were obtained in a highly regioselective manner by cyclocondensation reaction of β-enamino diketones with benzylisothiourea hydrochloride and methylisothiourea sulfate, respectively. Following the studies, was also investigated the reactivity of β-enamino diketones with guanidine hydrochloride and was possible to synthesize 2-aminopyrimidines that were obtained in a regioisomeric mixture of compounds with yields of 64-89 % and the reaction of β-enamino diketones with 2-acethylguanidine led to a highly regioselective synthesis of 2-acethylaminopyrimidines-4-carboxylates in yields (74-88 %). Ethyl 2-benzylthio-pyrimidine-4-carboxylates obtained were cyclized with hydrazine monohydrate and pyrimidopyridazinones were obtained in 52-95 % yields. Finally, were β-enamino diketones were cyclocondensed with 3(5)-amino-5(3)methylpyrazole leading to pyrazolo[1,5-a]pyrimidines of highly regioselective manner. These, in turn, are cyclized with an equivalent amount of hydrazine monohydrate to form a series of pyrazolo-pyrimido-pyridazinone (43-68%) and when using excess hydrazine monohydrate pyrazole-pyridazinone were formed by ANRORC (Addition of Nucleophile followed by Ring-Opening and Ring-Closure)mechanism yields 62-84%. The reactions for the synthesis of these heterocyclic systems involving simple steps, mild conditions and short reaction times.